Gamma-ray emission in near critical density plasmas - Brady, C; Ridgers, C; Arber, T; Bell, A (2013)
Previous work on the interaction of high power lasers with high density targets have identified that emission is primarily from interaction within the skin layer at the target front (e.g. Ridgers et al 2012 Phys. Rev. Lett. 108 165006). This mechanism is inefficient when compared to Reinjected Electron Synchrotron Emission (RESE) for laser interaction with low density solids (Brady et al 2012 Phys. Rev. Lett. 109 245006). However, these detailed analyses of the emission mechanisms were mainly based on 1D simulations and so did not incorporate some important 2D effects. In this paper these 1D emission mechanisms are confirmed to still exist in 2D with comparable properties and a new, intrinsically 2D, emission mechanism, termed edgeglow, is described which can convert 4-5% of the laser energy into gamma-ray energy. © 2013 IOP Publishing Ltd.